Self-regulation prompts promote the achievement of learning goals – But only briefly: Uncovering hidden dynamics in the effects of a psychological intervention. (August 2022) - Breitwieser, Jasmin; Neubauer, Andreas B.; Schmiedek, Florian; Brod, Garvin
Abstract: Most psychological interventions have to be administered repeatedly to be effective, but what is the optimal frequency? The answer will depend on how quickly the effects build up and wear off between intervention prompts. We investigated these temporal dynamics in a popular self-regulation intervention: implementation intentions. We combined a novel intervention design with objective high-resolution data of students' learning success during 40 days of preparation for an exam. Students (n = 223) received intervention prompts on half of the days, alternating between 2 and 3 consecutive days of prompting and no-prompting. These students outperformed a no-prompt control group (n = 116) in the final exam ( d  = 0.21). However, the beneficial effect of prompting on learning success increased over consecutive days of prompting and decreased when prompting was discontinued. These results suggest that the beneficial effects of self-regulation prompts on learning success are highly volatile and might benefit from regular repetitions. Highlights: An implementation intention boosted exam performance in medical students. The intervention effect built up over consecutive days of plan prompting. The intervention effect faded out when prompting was discontinued. Interventions to foster self-regulation might benefit from repeated prompting.